2017
DOI: 10.1016/j.jsat.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Fitbit-supported lifestyle physical activity intervention for depressed alcohol dependent women

Abstract: Purpose Women in alcohol treatment are more likely to relapse when in unpleasant, negative emotional states. Given the demonstrated benefits of exercise for decreasing depression, negative affect, and urges to drink, helping women engage in a lifestyle physical activity (LPA) intervention in early recovery may provide them a tool they can utilize “in the moment” in order to cope with negative emotional states and alcohol craving when relapse risk is highest. New digital fitness technologies (e.g., Fitbit activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 77 publications
3
46
0
4
Order By: Relevance
“…At baseline, participants reported heavy alcohol use, consuming alcohol 52.6% or the prior 90 days with an average of 10.11 (SD=6.36) drinks per drinking day. Overall results from the parent open trial (Abrantes et al, 2017) found that women significantly increased physical activity (Cohen’s d z = 0.87) and rates of alcohol abstinence (Cohen’s d z =1.08) over the course of the 12-week intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At baseline, participants reported heavy alcohol use, consuming alcohol 52.6% or the prior 90 days with an average of 10.11 (SD=6.36) drinks per drinking day. Overall results from the parent open trial (Abrantes et al, 2017) found that women significantly increased physical activity (Cohen’s d z = 0.87) and rates of alcohol abstinence (Cohen’s d z =1.08) over the course of the 12-week intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Women with a DSM-5 moderate to severe other substance use disorder, history of psychotic disorder, current suicidality/homicidality, current mania, current pregnancy, or physical or mental problems that would preclude them from engaging in physical activity were excluded from the study. See main outcome paper from the pilot project (Abrantes et al, 2017) for details on eligibility. A total of 20 women were recruited.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, "lifestyle physical activity" devices provide real-time support to women who are suffering from depression and addiction. Fitness trackers have been used to help individuals cope with mental Patient Experience Journal, Volume 6, Issue 2 -2019 illness/substance abuse, resulting in improved affect and reported high satisfaction with the devices 15 . Other researchers are examining the use of wearables to help engage in "digital phenotyping," collecting information about patients from their smartphones, to determine who is at risk of harm to notify supports when intervention might be necessary 16 .…”
Section: Introductionmentioning
confidence: 99%